Arid irrigated winter wheat and soybean cropping under conservation tillage systems - Nurbekov, Aziz; Umarov, Sherzod; Azizov, Shukhrat; Umarov, Muxammad; Khaitov, Botir; Khalilova, Lola; Namozov, Fazliddin; Teshaboyev, Sherzod (Frontiers in Sustainable Food Systems, 2025)
This research aimed to determine the effects of conservation tillage practices on the soil quality parameters and productivity of winter wheat (WW) followed by soybean (SB) in a conventionally irrigated arid environment. Field experiments were conducted in 2020–2023 in a split-plot design with the following four land management practices: conventional tillage (CT: moldboard plow + harrow), RT1 (chisel + harrow), RT2 (disk + harrow), and NT (no-till – without tillage). After three experimental cycles, the soil humus content increased by 10, 12, and 15% (p < 0.05) in the CT, RT1, and RT2 plots, respectively, while the highest soil humus was detected in the NT plot. Soil bulk density decreased from 1.6 g/cm3 to 1.33, 1.42, and 1.34 g/cm3 (p < 0.05) in the CT, RT1, and RT2 plots, respectively. A significant increase was found at the NT plot in terms of soil quality indicators such as total N and P, available N–NO3, P2O5, and K2O. The application of NT increased the yield components of WW and SB by 20 and 12%, respectively, compared to CT. This study showed that the highest WW (6.84 Mg ha−1) and SB (2.12 Mg ha−1) grain yields were achieved in the NT plot, most likely due to enhanced moisture and nutrient conservation, facilitated by the high amount of crop residues on the soil surface. The implemented NT method combined with the legume-based cropping system appears to be a more sustainable and environmentally friendly land management system to achieve a favorable soil environment that generates higher crop yield in the arid ecosystem.